Engineering applications of artificial intelligence: A bibliometric analysis of 30 years (1988–2018). (October 2019) - Shukla, Amit K.; Janmaijaya, Manvendra; Abraham, Ajith; Muhuri, Pranab K.
Abstract: The Engineering Applications of Artificial Intelligence (EAAI) is a journal of very high repute in the domain of Engineering and Computer Science. This paper gives a broad view of the publications in EAAI from 1988–2018, which are indexed in Web of Science (WoS) and Scopus. The main purpose of this research is to bring forward the prime impelling factors that bring about the EAAI publications and its citation structure. The publication and citation structure of EAAI is analyzed, which includes the distribution of publication over the years, citations per year and a bird's eye view of the citation structure. Then the co-citation analysis and over the year's trend of top keywords is given. The co-authorship networks and a geographic analysis of the sources is also provided. Further, a country-wise temporal and quantitative analysis of the publications is given along with the highly cited documents among the EAAI publications.